CIVIL SOCIETY COUNTER-FRAMING: LICENSING RELIGIOUS ORGANIZATIONS IN INDONESIA’S MINING SECTOR UNDER PRESIDENT JOKOWI - Dewi Masitoh (Universitas Jenderal Ahmad Yani, 2025)
Indonesia is renowned for its abundant natural resources, yet it continues to face challenges in governing them equitably and sustainably, particularly in the mining sector. On 30 May 2024, the government issued Government Regulation (PP) No. 25 of 2024, revising PP No. 96 of 2021 on mineral and coal mining operations. The revision prioritizes religious mass organizations to manage Special Mining Business Permit Areas (WIUPK) to enhance economic empowerment. However, the policy has sparked controversy and created dilemmas in resource governance. This study employs a qualitative approach emphasizing observation and interpretation of social phenomena through exploratory and descriptive strategies. It also mobilizes the concept of counter-framing—constructing alternative narratives to reshape public interpretations by contesting dominant views, including government policy. Civil society has responded with advocacy, campaigns, and research to reveal potential harms and encourage inclusive, transparent dialogue. Accordingly, prudent, participatory policymaking is needed to secure social justice and environmental sustainability. Keywords: Government Regulation (PP) No. 25/2024, Counter-Framing, Natural Resource Governance, Religious Mass Organizations, Indonesia’s Mining Sector.